ТВОРЧІСТЬ ЯК ВАЖЛИВИЙ ФАКТОР ЗДОРОВ'Я EXYSD СЕРЕДНОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
The aim of investigation was to analyze pupils creative thinking at secondary school of 8-12-th grades (480 pupils tested), their health locus of control, anxious and academic chievments and their interrelations.T.E. Torrance (1974) tests o f creative thinking (TTCT), D. Walstone (1978) “Multidimentional health locus o f control scale” were used as main evaluation tools. Additionally was used Kondash modified technique (1973) - the scale of anxious.The main rezult showed that pupils creativity didin’t have a strong corrélation with their academic achievments and there were complicated positive connections between crearivity, health locus of control, anxious and academic achievments.